2019
DOI: 10.1088/1361-648x/ab22fa
|View full text |Cite
|
Sign up to set email alerts
|

Competing interactions in a long-range spin-lattice coupled model and tricriticality

Abstract: The interplay of spin and lattice degrees of freedom on the critical behavior of magnetic phase transitions in strongly correlated systems can be studied analytically by constructing an effective model Hamiltonian for the corresponding order parameters. Here we consider such a model C-type Hamiltonian involving the coupling between order parameter and the strain field. Taking the strain interaction to be long-range (LR) in nature, we carry out a renormalization-group analysis at one-loop order. This reveals a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…is obtained by setting γ 0 = i 2λ 0 C −1 0 in equation (7). As derived explicitly in reference [57], one would arrive at the renormalization-group flow equations at lowest order as…”
Section: The Renormalization-group Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…is obtained by setting γ 0 = i 2λ 0 C −1 0 in equation (7). As derived explicitly in reference [57], one would arrive at the renormalization-group flow equations at lowest order as…”
Section: The Renormalization-group Resultsmentioning
confidence: 99%
“…It is generally expected that the different fixed points collide and exchange their stabilities in the presence of such a competing potential. A recent theoretical work [57] has revealed that the presence of short-range interaction affects the long-range critical behavior of such a model Hamiltonian.…”
Section: The Renormalization-group Resultsmentioning
confidence: 99%
See 3 more Smart Citations